Design and Performance Analysis of Interference cancellation inHeterogeneous networks With Multi-Antenna Arrays (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
To improve national security, government agencies have long been committed to enforcing powerfulsurveillance measures on suspicious individuals or communications. In this paper, we consider awireless legitimate surveillance system, where a full-duplex multi-antenna legitimate monitor aims toeavesdrop on a dubious communication link between a suspicious pair via proactive jamming.Massive Multiple-Input Multiple-Output (MIMO), small cell, and full-duplex are promisingtechniques for future 5G communication systems, where interference has become the mostchallenging issue to be coped with. In this paper, we provide an interference coordination frameworkfor a two-tier heterogeneous network (HetNet) that consists of a massive-MIMO enabled macro-cellbase station (MBS) and a number of full-duplex small-cell base stations (SBSs). For each scenario,the optimal jamming power is derived in closedform and efficient algorithms are obtained for theoptimal transmit/receive beamforming vectors. Moreover, low-complexity suboptimal beamformingschemes are proposed for the MIMO case. Our analytical findings demonstrate that by exploitingmultiple antennas at the legitimate monitor, the eavesdropping non-outage probability can besignificantly improved compared to the single antenna case.